Effects of Molecular Distillation on the Chemical Components, Cleaning, and Antibacterial Abilities of Four Different Citrus Oils - Yang, Feilong; Zhang, Huijuan; Tian, Guifang; Ren, Wenbo; Li, Juan; Xiao, Hang; Zheng, Jinkai (Frontiers in Nutrition, 2021)
Essential oils (EOs) from citrus fruits are excellent aromatic resources that are used in food, cosmetics, perfume, and cleaning product. EOs extracted from four citrus varieties, sweet orange, grapefruit, mandarin, and lemon, were separated into two fractions by molecular distillation. The composition, physicochemical properties, cleaning ability and antimicrobial activity of each EO was then systematically evaluated. The relationships between each of the aforementioned characteristics are also discussed. In keeping with the principle of ‘like dissolves like’, most citrus EOs show better cleaning ability than acetone and all tend to dissolve fat-soluble pigment. 1-Decanol, α-terpineol, geraniol and linalool are key components of citrus EOs for the inhibition of Staphylococcus aureus, Escherichia coli, Candida albicans, and Vibrio parahaemolyticus, respectively. The findings of this study will be of significant importance for the effective utilization of citrus peel resources and in the development of future applications for citrus EOs.